Hundreds more women readers' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Increasing the value of Spore to women with agricultural occupations is one highly visible part of our editorial policy. Three years ago, only 7% of our subscribers were women, and measures were taken to increase that share, including extensive...